Water-based poly(urethane-urea) dispersions - meeting the European Union legislation - Fernandes, I.P. (2015)
This article discusses the synthesis methods of water-based poly(urethane-urea) dispersions (PUD), which over the past few decades have developed a solid reputation for high performance applications, particularly in the field of adhesives and coatings. PUDs are mostly environmentally compatible products since they do not contain or contain only low amounts of volatile organic compounds (VOC). This is an important feature in view of the present environmental policies, where governments and internal agencies are placing emphasis on developing sustainable processes, improving work conditions and reducing emissions of toxic and polluting substances into the atmosphere. In this context, this paper will discuss the main approaches applied to PUD synthesis in order to meet severe environmental restrictions resulting from the EU legislation.